Receiver simplification in synchronous communication systems: Simulation study - Mohd Fadzil, Ain; Farid, Ghani; Mutamed, Khatib; Syed Idris, Syed Hassan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/